Student’s perception of e-Learning - Nur Ahyani; Wahid Wahid (Universitas PGRI Madiun, 2021)
The purpose of this study was to determine students' perceptions of E-learning based learning in the 2019/2020 even semester lectures. The population of this research is the postgraduate students of PGRI Palembang University with a sample of 81 students taking ICT and Educational Innovation courses. This research is a descriptive study. The research data was taken using a questionnaire about readiness to take E-learning, the benefits of E-learning, constraints on E-learning, and E-learning interactions. Data were analyzed using a percentage of student responses to the questionnaire given. The results showed that seen from the responses of students who agreed to the readiness to take E-learning, it was 78%. Responses to the benefits of E-learning learning 67% who agreed, 68% of the responses to the constraints of E-learning learning agreed. The indicators of interaction between E-learning and learning were responded to by several 62 students, it can be concluded that students' perceptions of E-learning learning are quite good.